Numerical simulation on boiling heat transfer of evaporation cooling in a billet reheating furnace - Feng, Ming-jie; Wang, En-gang; Wang, Hai; Li, Yan-dong; Liu, Bing (Journal of Central South University, 2016)
The boiling heat transfer of evaporation cooling in a billet reheating furnace was simulated. The results indicate that the bubbles easily aggregate inside of the elbow and upper side of the horizontal regions in the π shaped support tubes. The circulation velocity increasing helps to improve the uniformity of vapor distribution and decrease the difference of vapor volume fraction between upper and down at end of the horizontal sections. With the increase of circulation velocity, the resistance loss and the circulation ratio both increase, but the former will decrease with the increase of work pressure.